Assessment of knowledge, attitudes, and precautionary actions against COVID-19 among medical students in Egypt - Marwa Rashad Salem; Salah H. Al Hanafy; Ahmed T. Bayad; Shaimaa B. Abdel-aziz; Dina Shaheen; Tarek T. Amin (Elsevier, 2021)
Background: The COVID-19 pandemic has become a significant public health threat. Therefore, the purpose of this survey was to assess knowledge, attitudes, and precautionary measures related to COVID-19 among college students. Methods: A convenient sample of 3263 volunteers responded to a self-administered electronic questionnaire during the period from October to December 2020. The knowledge, attitude, and practice (KAP) score level was calculated with a range of 0-34 points. Results: The mean age of the participants was 21 (+/−1.2) years, 69% were female, and 60.3% were urban. The majority of respondents received information about COVID-19 symptoms (93.9%), how to protect yourself (92.5%), and how it is transmitted (86.8%). The most cited sources of information were social media (75.7%), and the most credible were government websites and international organizations. More than half (65%) expressed concern regarding contracting COVID-19, and 89.2% believed that COVID-19 is a dangerous infection due to the rapid spread of the virus. The mean total KAP score was 26.1 (+/−4.2), which differed significantly between gender groups and residential areas. Logistic regression analysis showed that volunteers with good knowledge were 1.3 and 1.0 times more willing to volunteer and maintain a physical distance than those with less knowledge. Female students were 40% less likely to volunteer than males, yet they were 1.8 times more cautious about practicing protective measures such as washing their hands with soap and water than male students. Classifying the COVID-19 pandemic as a serious infection, urban communities have twice been careful to wear masks outdoors and maintain a social distance of at least 2 m from one another compared to rural inhabitants. Conclusion: The current survey revealed that medical students have good knowledge regarding COVID-19, a positive attitude towards the use of protective measures, which were necessary to limit the spread of the disease. However, improvement is still required, and community education should occur as usual with a commitment to utilizing all the strategies that can support knowledge to improve and change attitudes as well as practices of the population.